Les enseignantes du primaire au Niger : agents de promotion de la scolarisation des filles ? - Aissata Assane Igodoe (Cahiers de la Recherche sur l'Education et les Savoirs)
This article focuses on the construction of the professional identity of female teachers in Niger, in a context where they are particularly invited by the administration to play the role of promoters of girls’ schooling in rural areas. How can female teachers assume this role while being subject to contradictory injunctions by the administration and when rural communities are suspicious of the feminine model they embody? Indeed, the administration wants them to promote the job of teacher and thus the image of the salaried woman through their professional skills, though not exclusively so. Through the formal and informal rules imposed on them, which are considered necessary for the parents’ adherence to girls’ schooling, the administration also enjoins female teachers to conform to the social roles and behaviors assigned to rural women, whereas the mission of promoting girls’ schooling supposes in part the evolution of this model of femininity. In addition, these injunctions, which form the “identity by others” of female teachers, come into tension with their real and lived identity because female teachers find their working conditions difficult, and in the villages where they are supposed to integrate, some parents reject their professional and social identities.